PENGARUH BOPO, CAR, DAN LDR TERHADAP KINERJA KEUANGAN PADA PERBANKAN SYARIAH YANG GO PUBLIC DI BEI 2019 – 2022 - Wulandari, Novita Sri; Anwar, Amelia; Khoirina, Siti; subagja, ghia (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This research aims to determine the influence of BOPO, CAR, and LDR on financial performance in Islamic banking that goes public on the IDX 2019 - 2022. This research uses quantitative data with secondary data sources in the form of financial reports. The sampling technique used was purposive sampling and a sample of 10 Islamic banks was obtained. Data taken from quarterly financial reports obtained from the official website of each bank is the research sample. The results of this research show that the results of simultaneous testing (F Test) obtained an Fcount of 20,581 with an Ftable value of 2.87 with a significant result of 0.000 <0.05, which means that BOPO, CAR and LDR together have a significant influence on ROE. Meanwhile, the results of the t test (1) The tcount value for the BOPO variable is 1.056 < 2.024 or tcount < ttable and the sig value is 0.298 > 0.05 or the sig value < 0.05. So that H1 is rejected and H0 is accepted, it can be interpreted that the variable BOPO (X1) partially has no significant influence on ROE (2) CAR of 2.985 > 2.024 or tcount > ttable and a sig value of 0.005 < 0.05 or sig value > 0 .05 so it has a positive and significant effect on ROE. (3) LDR of 7.213 > 2.024 or tcount > ttable and a sig value of 0.000 < 0.05 or sig value > 0.05 so that it has a positive and significant effect on ROE.